Towards novel energy shunt inspired vibration suppression techniques: Principles, designs and applications. (1st January 2023) - Huang, Xingbao; Yang, Bintang
Abstract: Vibration control is an overwhelmingly concerned issue that exists in many industrial fields such as machinery, aerospace and civil engineering. Indeed, in terms of energy perspective, the nature of vibration control is scientifically disposing the vibration energy migration issues and enhancing the energy transfer, conversion and dissipation. It should be noted that high-efficiency vibration suppression is conducive to improving the working capability of mechanical devices, prolonging the service life of sensitive components, and promoting the security and stability of flexible architectures. Due to the attractive merits such as easy design, friendly installation, low attached mass and wideband vibration attenuation, the dynamic vibration absorbers (DVAs) are extensively developed and employed. This review paper is committed to investigate the current multifarious vibration suppression technologies and establish the collaboration between various vibration control methods from the perspective of energy shunt. Moreover, several attempts are conducted to provide feasible guidance for the development direction of state-of-the-art nonlinear DVAs in the future. In terms of energy shunt concept, general vibration control methods can be innovatively divided into regression energy strategy, syntonic elastic energy strategy, heat energy dissipation strategy and regenerative energy strategy. The regression energy strategy refers to energy sinks in which the trapped energy is mainly exploited to overcome intra-well or inter-well barrier. Syntonic elastic energy strategy is employed to describe the local resonance deformation energy generation and dissipation, such as distortion of substructures in metamaterials. Dampers mainly consider the use of damping force to dissipate kinetic energy, impact, without considering the restoring force, in this regard, magnetorheological dampers, eddy current dampers and switched-coupling dampers are semblable in counteracting or dissipating the kinetic energy of the primary system; due to the significant heat generation during transformation operation, heat energy strategy is opted for describing their energy evolution. According to the law of energy conservation, the larger the proportion of energy converted, the smaller the other forms of energy; thereby energy conservation efficiency can be used to measure the decrease of vibration energy. The regenerative energy strategy is referring to vibration control method based on available energy conversion and utilization. Finally, a concise summary on energy shunt strategy based DVAs and some intractable ongoing issues are presented. Additionally, the challenges and development trends of neoteric nonlinear vibration absorbers in the future are prospected.